Transcription factor DREF regulates expression of the microRNA gene bantam in Drosophila melanogaster - M. B. Schwartz; M. M. Prudnikova; O. V. Andreenkov; E. I. Volkova; I. F. Zhimulev; O. V. Antonenko; S. A. Demakov (Вавиловский журнал генетики и селекции, 2024)
The bantam gene encodes a vital microRNA and has a complex expression pattern in various tissues at different stages of Drosophila development. This microRNA is involved in the control of normal development of the ocu lar and wing imaginal discs, the central nervous system, and also in maintaining the undifferentiated state of stem cells in the ovaries of adult females. At the cellular level, bantam stimulates cell proliferation and prevents apoptosis. The bantam gene is a target of several conserved signaling cascades, in particular, Hippo. At the moment, at least ten proteins are known to directly regulate the expression of this gene in different tissues of Drosophila. In this study, we found that the bantam regulatory region contains motifs characteristic of binding sites for DREF, a transcription factor that regulates the expression of Hippo cascade genes. Using transgenic lines containing a fulllength bantam lethality-rescuing deletion fragment and a fragment with a disrupted DREF binding site, we show that these motifs are functionally significant because their disruption at the bantam locus reduces expression levels in the larvae and ovaries of homozygous flies, which correlates with reduced vitality and fertility. The effect of DREF binding to the promoter region of the bantam gene on its expression level suggests an additional level of complexity in the regulation of expression of this microRNA. A decrease in the number of eggs laid and a shortening of the reproductive period in females when the DREF binding site in the regulatory region of the bantam gene is disrupted suggests that, through bantam, DREF is also involved in the regulation of Drosophila oogenesis.